Severe atypical skin disease in two patients with CLL/SLL after BTKi treatment - a case report and literature review - Zhou, Jingxin; Ma, Wentong; Hu, Na; Ma, Yuhan; Zhu, Huayuan; Gao, Ling (Frontiers in Oncology, 2024)
Dermatological adverse events (AEs) are generally mild during therapy with Bruton’s tyrosine kinase inhibitor (BTKi), and it is often unnecessary to adjust the BTKi dosage or discontinue treatment. However, in this study, we present the cases of two patients diagnosed with chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) who experienced severe dermatological AEs during BTKi treatment and subsequently had to discontinue it. The first patient, who previously suffered from rashes, experienced rashes again along with fever when exposed to BTKi. The subsequent dermatological biopsy revealed necrotizing vasculitis. The second patient suffered from skin ulcers concurrently with cough and fever. The BTKi treatment was permanently discontinued when the histopathological biopsy revealed a fungal infection. Therefore, clinicians should pay attention to atypical rashes during BTKi treatment and skin biopsies are necessary for further diagnosis and intervention.